CircRNA mannosidase alpha class 1A member 2 contributes to the proliferation and motility of papillary thyroid cancer cells through upregulating metadherin via absorbing microRNA-449a. Issue 1 (31st August 2022) - Feng, Yao; Yang, Xinxin; Wang, Yibo; Chi, Nannan; Yu, Jianan; Fu, Xiandong
Abstract : Papillary thyroid carcinoma (PTC) is a common malignancy in endocrine system globally. Accumulating articles have found that circular RNAs (circRNAs) were dysregulated, and they were involved in PTC development. The aim of this project was to explore the function and associated mechanism of circRNA mannosidase alpha class 1A member 2 (circMAN1A2) in PTC progression. The expression of RNA was determined by real-time quantitative PCR. Cell proliferation ability was analyzed by colony formation assay and 5-ethynyl-2′-deoxyuridine assay. Cell migration and invasion were assessed by wound healing assay and transwell invasion assay, respectively. Protein levels were determined by Western blot assay. Dual-luciferase reporter assay and RNA immunoprecipitation assay were applied to confirm the interaction between microRNA-449a (miR-449a) and circMAN1A2 or metadherin (MTDH). Xenograft tumor model was utilized to explore the effect of circMAN1A2 silencing on tumor growth in vivo . CircMAN1A2 expression was elevated in PTC specimens and three PTC cell lines relative to adjacent normal specimens and Nthy-ori 3-1 cell line. CircMAN1A2 silencing inhibited the proliferation and motility of PTC cells. CircMAN1A2 acted as a molecular sponge of miR-449a, and circMAN1A2 knockdown suppressed PTC development partly through upregulating miR-449a. MiR-449a bound to the 3′ untranslated region of MTDH, and miR-449a restrained PTC progression partly through down-regulating MTDH. CircMAN1A2 interference suppressed PTC progression in vivo . CircMAN1A2 contributed to the proliferation ability and motility of PTC cells through enhancing MTDH expression via sponging miR-449a.